INFECTIOUS AETIOLOGY OF MARGINAL ZONE LYMPHOMA AND ROLE OF ANTI-INFECTIVE THERAPY - Salvatore Perrone; Gianna Maria D'Elia; Alessandro Pulsoni (Mediterranean Journal of Hematology and Infectious Diseases)
Marginal zone lymphomas have been associated with several infectious agents covering both viral and bacterial pathogens and in some cases a clear aetiological role has been established. Pathogenetic mechanisms are currently not completely understood, however the role of chronic stimulation of the host immune response with persistent lymphocyte activation represents the most convincing explanation for lymphoproliferation. Gastric MALT lymphoma is strictly associated with Helicobacter pylori infection and various eradicating protocols, developed due to increasing antibiotic resistance, represent the first line therapy. The response rate to eradication is good with 80% of response at 1 year; this finding is also noteworthy because recapitulates a cancer cured only by antibacterial approach and it satisfies the Koch postulates of causation, establishing a causative relationship between Hp and gastric MALT lymphoma. Patients with chronic HCV infection have 5 times higher risk to develop MZL, in particular an association with splenic and nodal MZL has been shown in several studies. Moreover, there is evidence of lymphoma regression after antiviral therapy with interferon+ribavirin, thus rising hope that new available drugs, extremely effective against HCV replication, could improve outcome also in HCV-driven lymphomas. The rare cases of MZL localized to orbital fat and eye conjunctivas have been associated with Chlamydia psittaci infection carried by birds. Efficacy of antibacterial therapy against C. psittaci are conflicting and generally poorer thain gastric MALT. Finally some case-reports will cover the relationship between primary cutaneous B-cell Lymphomas and Borrelia Burgdorferi.